ПРОЕКТУВАННЯ ТЕХНОЛОГІЇ ФОРМУВАННЯ ПІЗНАВАЛЬНОЇ САМОСТІЙНОСТІ СТУДЕНТІВ ВНЗ ПРИ ВИВЧЕННІ ЕКОНОМІЧНИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2010)
The article reveals some approaches concerning forming students cognitive independence in the course of economic disciplines training, special attention is paid to working out the technology, and also to organizational forms, methods, receptions and means as its integral components.